The business environment - Worthington, Ian, 1946-; Britton, Chris (Harlow, England ; New York : FT Prentice Hall, 2009)
This work contains a thorough analysis of the external influences that affect business activity. Theory is backed up by a wealth of statistical data, commentary and mini case studies.
Includes bibliographical references and index.
Keywords: Industrial management -- Great Britain; Industrial policy -- Great Britain; Industrial policy -- European Union countries; International economic relations; Business; Great Britain -- Commerce; European Union countries -- Commerce